Ideology of Stephen Hawking’s speech entitled “The universe’’ on Ted Talks - Yanik Lailinas Sakinah (Aksara: Jurnal Bahasa dan Sastra, 2021)
A speech become a media to deliver an idea and thoughts which lead someone to show an ideology which reflected on the utterances. The aim of this research was find out the Ideology of Stephen Hawking that was reflected on his speech entitled ‘The Universe’ which uploaded on TEDTalks through the use of illocutionary act. The research method used was descriptive qualitative to get deep analysis by using note taking technique and the data was analyzed by using an approach of critical discourse analysis by Fairclough. This research utilized Speech Act by Austin (1962 and Searle (1977). The results showed that Stephen gave a lot of information from what he has known and proved about the universe then emphasized to the viewer that Big Bang is the beginning of the universe. It is supported by illocutionary act which used by Stephen Hawking, about 33,33% from the whole utterances the speaker used representative illocutionary act in act of informing. Key Words: Critical Discourse Analysis, Speech Act, Illocutionary act, and Representative act